The effects of alumina morphology and Pt electron property on reversible hydrogenation and dehydrogenation of dibenzyltoluene as a liquid organic hydrogen carrier. (22nd January 2022) - Shi, Libin; Zhou, Yiming; Tan, Xiao; Qi, Suitao; Smith, Kevin J.; Yi, Chunhai; Yang, Bolun
Abstract: The morphologies and the electron property of catalysts play the very important roles in the hydrogenation and dehydrogenation of liquid organic hydrogen carriers (LOHCs) such as dibenzyltoluene (DBT). The different morphologies and pore structures of γ-Al2 O3 and Mox C doped γ-Al2 O3 were synthesized as the supports for Pt catalysts. After analyzing of various characterizations and catalytic testing, it was found that the large surface area and the mesoporous structure of catalysts are beneficial to both DBT hydrogenation and perhydro-dibenzyltoluene (H18-DBT) dehydrogenation. The doping of Mox C promoted the formation of the smaller Pt nanoparticles and increased Pt dispersion. The forming Pt–Mo structure is beneficial to hydrogen spillover which suppress the formation of by-product. The high Pt dispersion of 0.1 wt% Mox C doped Pt/Al2 O3 catalyst plays the positive roles in increasing H18-DBT dehydrogenation activity. Graphical abstract: Image 1 Highlights: The large pore volumes of mesoporous facilitate H18-DBT dehydrogenation. The doping of Mox C on catalyst increased the Pt dispersion. The doping of Mox C on catalyst increased the Pt electron density. The higher Pt dispersion on catalysts increased H18-DBT dehydrogenation activity. The lower Pt electron density on catalysts facilitated H18-DBT dehydrogenation.